The Effect of E-Verify Laws on Crime - Brandyn Churchill; Andrew Dickinson; Taylor Mackay; Joseph J. Sabia (Institute of Labor Economics (IZA), 2019)
E-Verify laws, which have been adopted by 23 states, require employers to verify whether new employees are eligible to legally work prior to employment. In the main, these laws are designed to reduce employment opportunities for unauthorized immigrants, reduce incentives for their immigration, and increase employment and earnings for low-skilled natives. This study explores the impact of state E-Verify laws on crime. Using agency-by-month data from the 2004 to 2015 National Incident Based Reporting System (NIBRS), we find that the enactment of E-Verify is associated with a 5 to 10 percent reduction in property crimes involving Hispanic arrestees, an effect driven by universal E-Verify mandates that extend to private employers. Supplemental analyses from the Current Population Survey (CPS) suggest that E-Verify-induced increases in employment of low-skilled natives of Hispanic descent, and outmigration of younger Hispanics are important channels. We find no evidence that crime was displaced to nearby U.S. jurisdictions without E-Verify or that violent crime was impacted by E-Verify mandates. Moreover, neither arrests nor labor market outcomes of white or African American adults were affected by E-Verify laws. The magnitudes of our estimates suggest that E-Verify mandates generated 491 million in social benefits of reduced crime to the United States.
Keywords: K14; J61; 330; E-Verify; immigration; crime; employment